Sulphonamide inhibition studies of the β-carbonic anhydrase from the bacterial pathogen Clostridium perfringens - Daniela Vullo; R. Siva Sai Kumar; Andrea Scozzafava; James G. Ferry; Claudiu T. Supuran (Taylor & Francis Group, 2018)
The β-carbonic anhydrases (CAs, EC 4.2.1.1) from the pathogenic bacterium Clostridium perfringens (CpeCA) was recently characterised kinetically and for its anion inhibition profile. In the search of effective CpeCA inhibitors, possibly useful to inhibit the growth/pathogenicity of this bacterium, we report here an inhibition study of this enzyme with a panel of aromatic, heterocyclic and sugar sulphonamides/sulphamates. Some sulphonamides, such as acetazolamide, ethoxzolamide, dichlorophenamide, dorzolamide, sulthiame and 4-(2-hydroxymethyl-4-nitrophenyl-sulphonamido)ethylbenzenesulphonamide were effective CpeCA inhibitors, with KIs in the range of 37.4-71.6 nM. Zonisamide and saccharin were the least effective such inhibitors, whereas many other aromatic and heterocyclic sulphonamides were moderate - weak inhibitors with KIs ranging between 113 and 8755 nM. Thus, this study provides the basis for developing better clostridial enzyme inhibitors with potential as antiinfectives with a new mechanism of action.